MARK MORAL IN DANCE GAMBIRANOM (STUDY MORALITY IMMANUEL KANT) - List Salsabila, Nadia; Nursilah, Nursilah; Pearl Sari, Kartika (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Leave from perspective Immanuel Kant about morality, study this aim for identify the moral values in the Gambiranom dance that deserve to be guided to bring life to life return values moral which has faded. Discourse analysis methodology with approach Qualitative research in this study is used to understand the symbolic messages contained in the text something discourse. Discourse which meant in study this is dance Gambiranom. Collection data done through Interview, observation, studies References, and studies documentation. The data analysis technique used the data analysis technique of the Miles and Huberman model. This research produce two data main research, namely Hasta Sawanda dance Gambiranom and shape Gambiranom dance presentation. These data produce an interpretation of Hasta Sawanda in the Gambiranom dance as good will according to the perspective of Immanuel Kant's moral values, and the form of presenting the Gambiranom dance as an act rightly according to the perspective of Immanuel's moral values Kant. From the two data, it produces a good value (praiseworthy) which is then gives birth to the highest good (summum bonum). The highest good is obtained by a dancer if has carry out the action which correct (act rightly) and intention which good (good will) according to the rules of classical Javanese dance style Surakarta is a condition where dancers are successful merged himself into the full character of Irawan's character. So that connoisseurs/viewers don't again see dancer as personal dancer but character Raden Irawan or King Gambiranom.